The Role of Ibn Rushd's Hermeneutics in Transmitting Philosophical Interpretation to Western Civilization - Hidayat, Muhammad; Agustina, Sri Ayu; Hasbullah, Zainal Abidin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the tradition of philosophical exegesis (tafsir falsafi) as a historical endeavor to harmonize revelation and reason within the intellectual heritage of Islam, with a particular focus on Ibn Rushd’s (Averroes) theological thought and its transformative impact on Western civilization, especially in Scholasticism, the Renaissance, and the Enlightenment. Employing a qualitative-descriptive method based on library research, this study applies a historical-philosophical approach and critical hermeneutics to analyze Ibn Rushd’s major works, namely Fasl al-Maqal and Tahafut al-Tahafut, alongside secondary sources such as the ideas of classical Islamic philosophers (Al-Kindi, Al-Farabi, Ibn Sina, and Al-Ghazali), Western thinkers (Maimonides, Thomas Aquinas, and Siger of Brabant), and other relevant literature. Data were collected through critical literature review, while analysis followed Miles and Huberman’s interactive model, comprising data reduction, systematic data presentation, and verification to ensure valid conclusions. The findings reveal that the Islamic conception of “knowledge” is holistic, value-laden, and rooted in the Qur’anic mandate to optimize reason. Through his three-tier hermeneutics, Ibn Rushd restricted ta’wil to the educated elite and defended philosophy despite Al-Ghazali’s critiques. Although his ideas received limited appreciation in the Islamic world, they were widely adopted in Europe, influencing Maimonides and Thomas Aquinas, and giving rise to Latin Averroism, a controversial movement that nonetheless contributed to the Scientific Revolution. This study underscores the importance of valuing reason, recognizing epistemological pluralism, and exercising prudence in interpretation to safeguard harmony between faith and intellectual progress.